2010
DOI: 10.1007/s13280-010-0076-6
|View full text |Cite
|
Sign up to set email alerts
|

Current Nitrogen Management Status and Measures to Improve the Intensive Wheat–Maize System in China

Abstract: During the first 35 years of the Green Revolution, Chinese grain production doubled, greatly reducing food shortage, but at a high environmental cost. In 2005, China alone accounted for around 38% of the global N fertilizer consumption, but the average on-farm N recovery efficiency for the intensive wheat-maize system was only 16-18%. Current on-farm N use efficiency (NUE) is much lower than in research trials or on-farm in other parts of the world, which is attributed to the overuse of chemical N fertilizer, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
166
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 266 publications
(174 citation statements)
references
References 36 publications
7
166
1
Order By: Relevance
“…This tends to result in deep nutrient-rich soil layers. In our experiment a uniformly nutrient-rich soil profile (with greater total nutrient load) did not increase shoot growth (P=0.069) or plant nitrogen uptake (Table 2) to winter wheat (n=370)), does not significantly enhance grain yield (Cui et al 2006(Cui et al , 2010Peng et al 2012;Zhang et al 2012), however, there have been reported decreases in crop yield . These are likely to be due to the effect of nutrient placement on root growth (Fig.…”
Section: Discussioncontrasting
confidence: 46%
“…This tends to result in deep nutrient-rich soil layers. In our experiment a uniformly nutrient-rich soil profile (with greater total nutrient load) did not increase shoot growth (P=0.069) or plant nitrogen uptake (Table 2) to winter wheat (n=370)), does not significantly enhance grain yield (Cui et al 2006(Cui et al , 2010Peng et al 2012;Zhang et al 2012), however, there have been reported decreases in crop yield . These are likely to be due to the effect of nutrient placement on root growth (Fig.…”
Section: Discussioncontrasting
confidence: 46%
“…The build up of residual soil nitrate to the extent of 213 kg N ha −1 in 120 cm soil depth was reported from two years wheat-maize cropping system in India (Lenka et al, 2013). Likewise, Cui et al (2010) reported build up of residual NO3-N in soil profile in response to continuous application of excessive N in North China Plain. Similarly, lower levels of residual NO3 -were reported in high irrigation treatment than in low irrigation treatment at 120 cm (Lenka et al, 2013) and 200 cm (Wang et al, 2010) ) as compared to dry land conditions (82.5 kg N ha −1 yr −1 in the 0-400 cm soil profile (Fan et al, 2010).…”
Section: Discussionmentioning
confidence: 86%
“…Most farmers in China often overused and applied N fertilizer at the wrong times in intensive cropping systems [12,[51][52][53]. We found that the amount of N applied was the most important limiting management factor for the PFP N gap in 57.4% to 65.8% of all fields (Figure 6b).…”
Section: Effects Of Plant Density and N Application On Yield And Pfp Nmentioning
confidence: 85%